Comportamiento de un modelo de predicción de infección bacteriana invasiva en niños con cáncer, neutropenia y fiebre - Lizeth Hinestroza-Palomino (Asociación Colombiana de Infectología, 2020)
Objective: To describe the behavior of a predictor model of invasive bacterial infection in children with neutropenia and fever in Hospital Infantil San Vicente Fundación (HISVF by its name in Spanish), throughout the year of 2017. Material and method: Descriptive, cross-sectional study, which included patients under 14 years of age with a diagnosis of some type of cancer that attended HISVF in the period of time from January to December in 2017, with a diagnosis of neutropenia and fever. Results: 99 episodes were found in 44 patients diagnosed with neutropenia and fever. According to the stratified risk group and the outcome of microbiological isolation or death, differences were found between the two groups. Discussion: The application of these criteria can be used to improve therapeutic approach and impact in rational use of antibiotics and early discharge.